Neurofeedback in autism spectrum disorders - Holtmann, M.; Steiner, S.; Hohmann, S.; Poustka, L.; Banaschewski, T.; Bölte, Sven (Wiley-Blackwell Publishing Ltd., 2011)
Aim To review current studies on the effectiveness of neurofeedback as a method of treatment of the core symptoms of autism spectrum disorders (ASD). Method Studies were selected based on searches in PubMed, Ovid MEDLINE, EMBASE, ERIC, and CINAHL using combinations of the following keywords: 'Neurofeedback' OR 'EEG Biofeedback' OR 'Neurotherapy' OR 'Mu-Rhythm' OR 'SMR' AND 'Autism' OR 'Autism Spectrum Disorder' OR 'Pervasive Developmental Disorder'. Results The existing evidence does not support the use of neurofeedback in the treatment of ASD. Studies with outcomes in favour of neurofeedback might be showing an improvement in comorbid attention-deficit-hyperactivity disorder symptoms rather than a true improvement in core ASD symptoms. Interpretation Limitations of this review are those inherent in the studies available, including small sample size, short duration, variable diagnostic criteria, and insufficient control interventions, all causing a lack of generalizability.